Redefining fatty liver disease: an international patient perspective. (January 2021) - Shiha, Gamal; Korenjak, Marko; Eskridge, Wayne; Casanovas, Teresa; Velez-Moller, Patricia; Högström, Sari; Richardson, Ben; Munoz, Christopher; Sigurðardóttir, Sólveig; Coulibaly, Alioune; Milan, Miskovikj; Bautista, Fabiana; et al.
Summary: Despite its increased recognition as a major health threat, fatty liver disease associated with metabolic dysfunction remains largely underdiagnosed and undertreated. An international consensus panel has called for the disease to be renamed from non-alcoholic fatty liver disease (NAFLD) to metabolic-associated fatty liver disease (MAFLD) and has suggested how the disease should be diagnosed. This Viewpoint explores the call from the perspective of patient advocacy groups. Patients are well aware of the negative consequences of the NAFLD acronym. This advocacy group enthusiastically endorses the call to reframe the disease, which we believe will ultimately have a positive effect on patient care and quality of life and, through this effect, will reduce the burden on health-care systems. For patients, policy makers, health planners, donors, and non-hepatologists, the new acronym MAFLD is clear, squarely placing the disease as a manifestation of metabolic dysfunction and improving understanding at a public health and patient level. The authors from representative patient groups are supportive of this change, particularly as the new acronym is meaningful to all citizens as well as governments and policy makers, and, above all, is devoid of any stigma.